PGC-1a mediated muscle aerobic adaptations to exercise, heat and cold exposure - Ihsan, M.; Watson, G.; Abbiss, C. (Cellular and Molecular Exercise Physiology, 2014)
PGC-1a is regarded as a key regulator of mitochondrial biogenesis due to its central role in regulating the activity of key transcription factors associated with encoding mitochondrial components. Additionally, PGC-1a has shown to mediate adaptations that increase fat metabolism and angiogenesis, contributing to the overall oxidative phenotype of the muscle. While it is well established that exercise is a potent stimulator of PGC-1a, recent evidence indicate that heat and cold exposure may also influence mitochondrial biogenesis through up-regulation of PGC-1a. This highlights the potential use of these modalities in conjunction with exercise to enhance training adaptations. As such, the purpose of this review is to describe the possible mechanisms and pathways by which exercise as well as hot and cold exposures may influence mitochondrial biogenesis. It is clear that changes in intracellular calcium, oxidative stress and phosphorylation potential are major up-regulators of PGC-1a during exercise. Moreover, there is evidence implicating calcium signalling, in addition to ß-adrenergic activation in cold-induced mitochondrial biogenesis, while PGC-1a during heat exposure is likely triggered by changes in phosphorylation potential and nitric oxide signalling. However, these mechanisms appear to change considerably when cold/heat is administered following exercise, and seem to be dependent on the experimental models used (i.e. in vitro vs. in vivo, rodent vs. human). Understanding the effects heat/cold exposure and its interaction with exercise may lead to the optimisation and development of temperature-related interventions to enhance training adaptations, or aid in the treatment of mitochondrial related diseases.